Advancing crisis communication effectiveness : integrating public relations scholarship with practice - Jin, Yan, (Sociologist); Reber, Bryan H.; Nowak, Glen (New York, NY : Routledge, 2021)
"Advancing Crisis Communication Effectiveness shows how crisis communication plans and efforts for complex and challenging issues benefit when academic perspectives are connected with practitioner experiences. This book brings crisis and public relations scholars together with practicing professionals to integrate academic theories and research with the knowledge and lessons learned on the frontlines of crisis communication and management. This book illustrates how having insights and observations from both leading crisis communication scholars and professionals strengthens crisis management and communication strategies, plans, and coordination. Chapters co-authored by leading scholars and professionals highlight how academic theories and research can inform crisis management and response - and how practitioners can utilize, inform, and strengthen academic theories and research. For each topic area covered, examples and applications are provided that show how integrating public relations scholarship with practice can advance crisis communication effectiveness. This book represents a unique and timely contribution to the field of crisis management and communication. It will be an important resource for public relations and crisis management and communication scholars, educators, professionals, consultants, and graduate students"--
Complex and challenging crises : a call for solutions / Bryan H. Reber, C. Richard Yarbrough, Glen Nowak, & Yan Jin -- The evolving complexity of crisis issues : the role of crisis history / LaShonda L. Eaddy & Shelley Spector -- Corporate crises : sticky crises and corporations / W. Timothy Coombs, Sherry J. Holladay, & Rick White -- Connected in crisis : how nonprofit organizations can respond and refocus / Hilary Fussell Sisco & Mark McMullen -- Media relations for government/public affairs crises : ethical and unethical components of scandal and spin / David E. Clementson, Joseph Watson Jr., & Michael Greenwell -- A promising but difficult domain : complex health-related crises and academic-professional collaboration / Glen Nowak & Michael Greenwell -- Disaster and emergency crisis management communication / Robert L. Heath, J. Suzanne Horsley, Greg Guest, & Chris Glazier -- Managing misinformation and conflicting information : a framework for understanding misinformation and rumor / Lucinda Austin, Toni van der Meer, Yen-I Lee, & Jim Spangler -- Technology and social media : challenges and opportunities for effective crisis and risk communication / Deanna D. Sellnow, Lucinda Austin, & Ciro Dias Reis -- Law and (lack of) order in complex crises / Joseph Watson, Jr., James D. Firth, & Jonathan Peters -- Situational crisis communication theory (SCCT) and application in dealing with complex, challenging, and recurring crises / W. Timothy Coombs, Sherry J. Holladay, & Karen L. White -- Managing complexity : insights from the contingency theory of strategic conflict management / Yan Jin, Augustine Pang, Glen T. Cameron, Sungsu Kim, & Leonard (Len) A. Pagano, Jr. -- Calming giants in the earth : the internalization, distribution, explanation and action (IDEA) model as strategic communication in crises with competing narratives / Timothy L. Sellnow, Deanna D. Sellnow, & Ciro Dias Reis -- The social-mediated crisis communication (SMCC) model : identifying the next frontier / Brooke Fisher Liu, Yan Jin, Lucinda Austin, Erica Kuligowski, & Camila Espina Young -- The future of collaborative crisis research / Yan Jin, Matthew O'Conner, Bryan H. Reber, & Glen Nowak.
OCLC-licensed vendor bibliographic record.
Keywords: Communication in crisis management; Public relations -- Management; LANGUAGE ARTS & DISCIPLINES / Communication